Introducing energy through observations and measurements. (22nd August 2018) - Hartmann, Bruno; Priemer, Burkhard
Abstract: Research shows that energy is a concept that is difficult to understand despite different teaching approaches existing. One of the problems is seen in its rather abstract definition. In contrast, we present an approach that activates students' everyday life experiences and uses these to develop a scientific understanding by introducing energy as a basic observable that can be measured directly. We start by discussing the gravitational potential energy of an object near the surface of earth. The fundamental principles behind this approach can be extended to all forms of energy (thermal, kinetic etc) and other basic observables in classical and relativistic mechanics.